ITEM ANALYSIS OF THE CRITICAL THINKING TEST INSTRUMENT ON TEMPERATURE AND HEAT USING RASCH MODELLING - Alyamuari, Arum; Liliawati, Winny; Saepuzaman, Duden (Universitas Labuhanbatu, 2024)
The purpose of this study was to analyse the test items of the critical thinking test instrument usingRasch modelling. This research is a quantitative research. The sample determination used simple random sampling method and the subjects obtained were class XII students at one of the high schools in Bandung city consisting of 36 students. The research instrument used was a critical thinking ability test question consisting of 10 description questions. The results showed that the value of the difficulty level of the items was in the range of -2.45 to 1.86 and the average SEM was 0.31. Meanwhile, item reliability was 0.93, person reliability was 0.90, and Cronbach's alpha was 0.92. Based on the results of this study, it can be concluded that overall the items are declared fit with the Rasch model. Therefore, the critical thinking test instrument can be used by researchers to measure students' critical thinking skills.